Oil Exploitation and Environmental Sustainability in the Middle East: Issues and Solutions - Garlan Isiah (Global Writing Academica Researching and Publishing, 2024)
Oil exploitation in the Middle East has been a cornerstone of the region's economic growth and global energy supply. However, the extensive extraction and production activities have led to severe environmental degradation, threatening ecological balance and human health. This article delves into the multifaceted environmental impacts of oil exploitation in the Middle East, focusing on air and water pollution, land degradation, and loss of biodiversity. It also examines the socio-economic repercussions on local communities, including health issues and economic burdens. Furthermore, the paper discusses potential mitigation strategies, emphasizing the importance of robust regulatory frameworks, technological innovations, and environmental restoration projects. By addressing the environmental sustainability of oil production, this article aims to provide a comprehensive understanding of the challenges and propose viable solutions to balance economic interests with ecological preservation.